Manufacturing of magnetic steel by electroslag remelting: thermodynamic conditions. (4th August 2014) - Medina, S.F.; Reyes, F.
A study was conducted of the thermodynamic conditions for manufacturing magnetic steel (∼3% Si) by the ESR process, using electrodes made of cement steel. An examination was carried out of the influence of the following variables on the silicon content of the ingot: percentage of Si in the electrode, rate of deoxidation with Ca–Si, SiO2 activity, CaO activity, etc. By calculating the thermodynamic activities of the reactive components of the slag, it was possible to establish the conditions for manufacturing magnetic steels of uniform composition. One of the conditions is that CaO activity should not drop too much during remelting, because that would lead to segregation of the Al in the ingot.